Analisis Perbandingan Pendapatan UMKM Destinasi Wisata Gunung Telomoyo Sebelum dan Sesudah Covid-19 di Kecamatan Ngablak Kabupaten Magelang - Septiyani Septiyani; Febryantahanuji Febryantahanuji (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to analyze the comparative income of Micro, Small, and Medium Enterprises (MSMEs) in the Mount Telomoyo tourist destination before and after the COVID-19 pandemic in Ngablak District, Magelang Regency. This research employs a quantitative approach with a descriptive-comparative design. Data were collected through questionnaires, structured interviews, and documentation involving 30 MSME actors selected using purposive sampling.. Data analysis was conducted using descriptive and inferential statistics, including multiple linear regression, t-test, F-test, and coefficient of determination with the assistance of SPSS software. The findings reveal that the COVID-19 pandemic had a significant impact on the decline of MSME income, primarily due to a drastic reduction in tourist visits. However, in the post-pandemic period, a recovery trend in income was observed, driven by an increase in visitor numbers, ticket price adjustments, and improved business profitability. Partially, variables such as VAT, ticket price, number of visitors, profitability, and taxes paid do not exhibit a significant effect on MSME income. Nevertheless, simultaneously, all independent variables significantly influence MSME income. These findings indicate that the dynamics of MSME income in tourism areas are not determined by a single variable, but rather by the complex interaction of multiple economic factors simultaneously